Цифровые сейсмические регистраторы и их калибровка - Щербина, С.В. (Геофизический журнал, 2011)
Описано цифрові сейсмічні станції, які розроблені у відділі сейсмології Інституту геофізики НАН України в 2006—2007 рр., а також модернізацію сейсмоприймачів для використання їх під час мікросейсмічного районування. Наведено приклади записів локальних вибухів, розглянуто спосіб калібрування мікросейсмічної апаратури. Description of the developed digital seismic stations in 2006—2007 years is presented in the article. The stations are used in the department of seismology of IG of NAS of Ukraine. Modernization is described of seismosensors for the use them in the processes of the microseismic districting. The examples of records of local explosions are rotined and short-story description of process of calibration of microseismic apparatus is given. Описаны цифровые сейсмические станции, разработанные в отделе сейсмологии Института геофизики НАН Украины в 2006-2007 г.г., а также модернизацию сейсмоприемников для использования их во время микросейсмического районирования. Приведены примеры записей локальных взрывов, рассмотрен способ калибровки микросейсмической аппаратуры.